Adolescent male genitalia dissatisfaction: a surgical perspective - Nicola Zampieri; Ilaria Dando; Francesco Saverio Camoglio (Asian Journal of Andrology, 2022)
Genital dissatisfaction is well known in female and adults. Less is known about male adolescents and their genital satisfaction. The aim of this study was to investigate and report the role of surgery in male adolescents to improve the evaluation of their genitalia. We considered all patients treated for external genital pathology in the period of adolescence. Inclusion and exclusion criteria were created. Patients underwent an evaluation test before and after surgery. During the study period, 137 patients were treated, and at the end of the study, 98 cases were considered for analysis. The most frequent pathologies were webbed penis and penile curvature. A postoperative score improvement was noted and patients with concealed penis and webbed penis showed a better postoperative outcome. Overweight was considered an important factor associated with a worse preoperative score. Evaluation of the external genitalia is important in adolescents, and it is an understudied problem. Overweight may be associated with a worse evaluation of one's genital and should be clinically considered to avoid related social problems in adulthood. Therefore, cosmetic genital surgery should be considered even in male adolescents.